Chiral Synthetic Equivalents of 2‐Cyanoethyl Tetraisopropylphosphorodiamidite: Application to the Synthesis and Resolution of Chiral Phosphoric Acids. Issue 19 (8th May 2014) - Isaac, Kévin; Stemper, Jérémie; Retailleau, Pascal; Betzer, Jean‐François; Marinetti, Angela
Abstract: Four synthetic equivalents of ( i Pr2 N)2 P‐OCH2 CH2 CN (1 ) have been prepared from readily available enantiomerically pure β‐hydroxynitriles as well as from chiral β‐hydroxy esters. To demonstrate their possible use as phosphinating/resolving agents, these phosphorodiamidites have been used in the synthesis of known phosphoric acids. The method allows enantiomerically pure acids to be obtained through separation of the diastereomeric phosphates. The method should favorably compete with other resolution procedures, e.g. fractional crystallization or chiral HPLC, for the small‐scale synthesis of new phosphoric acids for screening purposes. As synthetic equivalents of1, these auxiliaries might find applications also in other areas, for the synthesis of biologically relevant compounds. Abstract : Various chiral phosphorodiamidites displaying β‐cyanoethyl or β‐(alkoxycarbonyl)ethyl chains behave as synthetic equivalents of the well‐known β‐cyanoethyl tetraisopropylphosphorodiamidite. They can be used notably for the synthesis and resolution of chiral phosphoric acids through chromatographic separations of diastereomeric mixtures.